TINGKAT ADOPSI PETANI TENTANG PUPUK ORGANIK PADA BUDIDAYA PADI (Oryza sativa L.) DI DESA PANDOWOHARJO KECAMATAN SLEMAN KABUPATEN SLEMAN - Heriyanto, Heriyanto; Munanto, Totok Sevenek (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
This paper aimed to find out the level of farmer adoption of organic fertilizer in rice cultivation. Study do from April to June 2016 in the Pandowoharjo Village, Sleman Sub-District at Sleman District. Data was retrieved through interview of 30 respondents as samples, selected based on the proportional random sampling of 439 farmers. Data were statistically analysed to describe the farmer adoption level of organic fertilizers organized into three categories: high, medium, and low. The results showed that the rate of adoption use based on parameters of the correct type, dose, method and time of organic fertilizers showed high category (13.34%), medium (37.50%), and low (49.17%). Furthermore, counselling to increase knowledge about the application of organic fertilizer in rice farming and based on the evaluation showed increase of 87 percent.